The Gospel of Freedom and Power : Protestant Missionaries in American Culture after World War II - Ruble, Sarah E. (Book collections on Project MUSE., 2012)
In the decades after World War II, Protestant missionaries abroad were a topic of vigorous public debate. Public conversations about missionaries followed a powerful yet paradoxical line of reasoning, namely that people abroad needed greater autonomy from U.S. power and that Americans could best tell others how to use their freedom. In The Gospel of Freedom and Power, Sarah Ruble analyzes these public discussions about what it meant for Americans abroad to be good world citizens, placing them firmly in the context of the United States' postwar global dominance.